Assessing legislative gaps in Qatari law regarding AI-driven misinformation: insights from the UAE legal framework - Mashaallah Othman Alzwae; Abdelnaser Aljahani; Zinah Younus (Faculty of Law, University of Muhammadiyah Malang, 2025)
This study aims to examine the weaknesses of Qatari laws and assess their effectiveness in combating this new type of crime by comparing them with the UAE's Anti-Rumours and Cybercrime Law No. 34 of 2021, Article 54”, as a strong example of legislation in this area. The study highlights Singapore's law as a Southeast Asian example that explicitly criminalises